2013
DOI: 10.1111/agec.12016
|View full text |Cite
|
Sign up to set email alerts
|

The value of genetic information to livestock buyers: a combined revealed, stated preference approach

Abstract: DNA profile information has begun appearing in purebred bull auction catalogs; however, the value of this information is as of yet unknown. This study uses data from actual bull sales at a test station and combines it with stated‐preference survey data to determine the value of the DNA profile information. Consistent with previous research, we find that expected progeny differences (EPDs), test performance, and ultrasound information significantly influence bull‐buyers’ willingness‐to‐pay. The newer DNA profil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(34 citation statements)
references
References 18 publications
0
34
0
Order By: Relevance
“…Originally, the DCE method has been used in the transport economics (Hensher & Truong, ) and marketing literature (Louviere & Woodworth, ), but increasingly applied in other research areas, including environment (Adamowicz et al., ; Colombo, Hanley, & Louviere, ), food safety and quality (Ifft, Roland‐Holst, & Zilberman, ), and other related disciplines. There is also a growing literature in application of DCE in valuation of animal and plant genetic resources (Elbakidze, Nayga Jr., Li, & McIntosh, ; Eric, Guy, & Riccardo, ; Kassie et al., ; Ouma, Abdulai, & Drucker, ; Scarpa et al., ; Vestal, Lusk, DeVuyst, & Kropp, ).…”
Section: Methodsmentioning
confidence: 99%
“…Originally, the DCE method has been used in the transport economics (Hensher & Truong, ) and marketing literature (Louviere & Woodworth, ), but increasingly applied in other research areas, including environment (Adamowicz et al., ; Colombo, Hanley, & Louviere, ), food safety and quality (Ifft, Roland‐Holst, & Zilberman, ), and other related disciplines. There is also a growing literature in application of DCE in valuation of animal and plant genetic resources (Elbakidze, Nayga Jr., Li, & McIntosh, ; Eric, Guy, & Riccardo, ; Kassie et al., ; Ouma, Abdulai, & Drucker, ; Scarpa et al., ; Vestal, Lusk, DeVuyst, & Kropp, ).…”
Section: Methodsmentioning
confidence: 99%
“…A hedonic pricing model was specified to estimate the impact of phenotypic traits, performance measurements, and EPDs on bull sale price over time, which follows the modeling approach of previous studies (Bekkerman, Brester, and McDonald, 2013;Brimlow and Doyle, 2014;Chvosta, Rucker, and Watts, 2001;Dhuyvetter et al, 1996;Jones et al, 2008;Kessler, Pendell, and Enns, 2017;McDonald et al, 2010;Vanek, Watts, and Brester, 2008;Vestal et al, 2013). Hedonic pricing models have been used to determine the influence of characteristics over time (Blank, Saitone, and Sexton, 2016;Hanson, Sherrick, and Kuethe, 2018;Zimmerman et al 2012).…”
Section: Empirical Modelmentioning
confidence: 99%
“…Interestingly, they noted birth weight EPD as one of the most valued by producers. Vestal et al (2013) used a stated preference and revealed preference study to determine how EPDs affected bull sale prices. Bull sale data from three Oklahoma Beef Inc. performance-tested bull sales in 2009-2010 were used in their revealed preference study.…”
Section: Introductionmentioning
confidence: 99%
“…() and Vestal et al. (), participants in our research made real, rather than hypothetical, choices. Participants submitted bids for six alternative wines drawn from the store's inventory; alternatives had shelf prices that were within three dollars of the original wine's shelf price…”
Section: Experimental Design and Proceduresmentioning
confidence: 73%